Venezuelans in Peru: a restrained citizenship? - Cañizález, Andrés (2023)
This article provides context to the widespread crisis and human rights violations in Venezuela, which triggered an unprecedented and massive migration of Venezuelans. In Peru, having established the second-largest community of Venezuelan migrants, it is crucial to investigate the effective exercise of citizenship. The article reviews the legal and institutional framework that would allow the exercise of citizenship and, from a communicational perspective, studies characterizing Venezuelan migration in Peruvian media. The article also collects information from surveys conducted by the Peruvian government on Venezuelan migrants. Additionally, the research used the focal group technique to gather experiences and perspectives from Venezuelan journalists living in Peru that reveal limited citizenship. The main limitations to the exercise of citizenship were obstacles to voting, the criminalization of migration, and xenophobia.